(untitled) (Politeja, 2024)
GERMANY TOWARDS THE REFORM OF THE EUROPEAN UNION’S CLIMATE POLICY (EUROPEAN GREEN DEAL, FIT FOR 55 PACKAGE) The aim of the paper is to present Germany’s position during the government of Chancellor Angela Merkel (CDU/CSU/SPD coalition: 2018-2021) and Chancellor Olaf Scholz (SPD/Alliance 90/Greens/FDP coalition: from 2021) towards changes in climate policy (understood as reform) introduced by the European Green Deal and the Fit for 55 package of legislative proposals, with particular emphasis on the issue of CO2 emission standards for new passenger cars and new light commercial vehicles. Germany’s support for increasing the level of ambition in the field of climate protection in the EU was largely the result of the belief that the success of the German transformation of the energy sector and achieving climate neutrality by 2045 also depends on the progress of the energy transformation process and the climate neutrality policy in the European Union.